REINTERPRETASI MAṢLAḤAH SEBAGAI METODE ISTINBĀṬ HUKUM ISLAM: Studi Pemikiran Hukum Islam Abū Isḥāq Ibrāhīm al-Shāṭibī - Amin Farih (Al-Ahkam, 2015)
This article aims to analyze al-Shāṭibī’s thought about maṣlaḥah and its contribution to the renewal of Islamic law. Maṣlaḥah is a method of istinbāṭ which aims to deprive human difficulties in carrying out their obligations, especially in the field of muamalah. General principles of maṣlaḥah that was conceived in al-Qur'an and hadis rise in the doctrine of maqāṣid al-sharī’ah. The main purpose is to enforce maṣlaḥah as an essential element for the all purposes of Islamic law. The doctrine of maqāṣid al-sharī’ah asserted that the purpose of the law is one, namely maṣlaḥah or goodness and prosperity of mankind. According to al-Shāṭibī, maṣlaḥah which formulated the law of Islam must consider the aspects of ḍarūriyyah, ḥājiyyah and taḥsīniyyah as a structure consisting of three tiers one of another mutually related. The significance of al-Shāṭibī’s thinking about maṣlaḥah mursalah is that this method is a kind of unification and as an alternative over differences of opinion among the scholars on the validity of maṣlaḥah mursalah as a method of Islamic law.